2021
DOI: 10.33963/kp.15986
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic alcohol overuse on heart function and prognosis: layer-specific longitudinal strain and mid-term outcome analysis

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Moreover, after 6 months of follow-up, a reduction in E/e' ratio was observed in the abstainers as compared to the control group (P = 0.041) [20]. Thus, the authors postulate E/e' ratio as a predictor of a very early stage of alcohol-related heart dysfunction, and this observation was confirmed in a similar study performed by Rosa G. et al [21].…”
Section: Cardiomyopathysupporting
confidence: 59%
“…Moreover, after 6 months of follow-up, a reduction in E/e' ratio was observed in the abstainers as compared to the control group (P = 0.041) [20]. Thus, the authors postulate E/e' ratio as a predictor of a very early stage of alcohol-related heart dysfunction, and this observation was confirmed in a similar study performed by Rosa G. et al [21].…”
Section: Cardiomyopathysupporting
confidence: 59%
“…The best absolute cut-off values for outcome prediction were: GLS <18%, layer endocardial strain <19%, and layer epicardial strain <15%. (53) Alcohol related arrhythmias Atrial fibrillation (AF) is the most common arrhythmia observed among alcohol abusers. Larsson and al. proved that during chronic alcohol exposure, an increase in consumption of one AU per day increases the risk of AF by 8%.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…So, if alcohol can decrease cardiovascular mortality and the occurrence of diabetes, which non-cardiovascular mortality does it increase then? The risk of mortality is caused by malignant diseases, especially oropharyngeal, laryngeal, liver, colorectal, breast malignancy [16,17], liver cirrhosis, epilepsy, not to mention death by violence, traffic accidents, etc. The proportion of drinkers worldwide has remained the same since 1990; due to population growth, absolute numbers increased from 983 million to 1.34 billion in 2020.…”
Section: Evidence-based Medicinementioning
confidence: 99%
“…In Figure 1, possible harms and benefits are presented. The argument that a decrease of DM2 will decrease its related diseases has not been proven by any study [17]. [2,3,8,12,16,17,21,22].…”
Section: Evidence-based Medicinementioning
confidence: 99%
See 1 more Smart Citation